2006
DOI: 10.1136/bmj.38961.584653.ae
|View full text |Cite
|
Sign up to set email alerts
|

Mobilisation with movement and exercise, corticosteroid injection, or wait and see for tennis elbow: randomised trial

Abstract: Objective To investigate the efficacy of physiotherapy compared with a wait and see approach or corticosteroid injections over 52 weeks in tennis elbow. Design Single blind randomised controlled trial. Setting Community setting, Brisbane, Australia. Participants 198 participants aged 18 to 65 years with a clinical diagnosis of tennis elbow of a minimum six weeks' duration, who had not received any other active treatment by a health practitioner in the previous six months. Interventions Eight sessions of physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
438
3
39

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 474 publications
(497 citation statements)
references
References 20 publications
17
438
3
39
Order By: Relevance
“…Overall improvement was defined as patient-rated ''complete recovery'' or ''much improvement'' on a six-point Likert global assessment scale [4], a 50% or greater reduction in baseline pain status, a three-point reduction in the baseline VAS score, a final pain score of 3 of 10 or less, or a final Roles-Maudsley score [30] of 1 or 2. The analysis of pain relief used scores from the 10-or 100-point VAS, self-reported pain status, and four-point Roles-Maudsley rating scale [30].…”
Section: Data Itemsmentioning
confidence: 99%
“…Overall improvement was defined as patient-rated ''complete recovery'' or ''much improvement'' on a six-point Likert global assessment scale [4], a 50% or greater reduction in baseline pain status, a three-point reduction in the baseline VAS score, a final pain score of 3 of 10 or less, or a final Roles-Maudsley score [30] of 1 or 2. The analysis of pain relief used scores from the 10-or 100-point VAS, self-reported pain status, and four-point Roles-Maudsley rating scale [30].…”
Section: Data Itemsmentioning
confidence: 99%
“…A study comparing the effectiveness of physical therapy and CS injections, reported that CSs are superior in the short-term but physical therapy is superior in the long-term. [15,16] With regard to tennis elbow, Tonks et al [17] assessed the relative merits of a 'watch and wait' policy, physiotherapy alone, steroid injection therapy alone, and combined physiotherapy and steroid injection therapy, using a prospective randomized controlled trial design. After 7 weeks, patients who received steroid injections had significantly superior outcomes on all measures at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…не воспалительный, а дегенеративно-дистрофический процесс [6]. Среди иностранных авторов довольно часто используют термин tennis elbow -«локоть теннисиста», отмечая, что значительное количество игроков в большой теннис страдают этим заболеванием [4]. …”
unclassified